Introducing Voluntary Assisted Dying: Staff Perspectives in an Acute Hospital - Robin Digby; Rosalind McDougall; Michelle Gold; Danielle Ko; Lisa O'Driscoll; Tracey Bucknall (Kerman University of Medical Sciences, 2022)
BackgroundVoluntary assisted dying (VAD) was legalised in Victoria, Australia in June 2019. Physicians can now assist patients to end their lives by providing drugs for self-administration at their voluntary and competent request (or for physician administration in limited circumstances). This study investigates the opinions of clinicians on the implementation of the legislation in one Victorian hospital. MethodsThis exploratory survey study was conducted at a 600-bed acute hospital in Melbourne, Australia in Jan 2019. 382 clinicians completed one or more qualitative questions. Participants commented on VAD, potential workplace challenges and staff support required. Free-text responses were analysed using inductive content analysis. ResultsSix themes: (1) Polarised views; (2) Fear of conflict; (3) Emotional burden; (4) Vulnerable patients; (5) Organisational challenges; (6) Decision-making. There were diverse views including objections to VAD for religious or ethical reasons, and whole-hearted support based on a compassionate response to suffering and the right of patients to self-determination. Participants feared conflict between colleagues, families and patients, and aggression towards staff. Clinicians called for educational and psychological support. There was concern that vulnerable patients may be coerced to opt for VAD to lessen the burden on families or the health system. Clinicians feared workloads would increase with the introduction of VAD. Patient decision-making capacity in this context must be firmly established before proceeding, and thorough assessments for depression, and optimal symptom management must be implemented before VAD is approved. A dedicated VAD team was suggested to support staff and manage VAD patients. ConclusionParticipants expressed polarised opinions about VAD and showed considerable anxiety about its introduction. Additional education and support are required to ensure that clinicians understand details of the legislation and their professional and personal options. Tolerance and respect for alternative viewpoints must be advocated within the organisation and more broadly.